Visceral goosebumps: on White-Jacket's minor resistance. Issue 11 (2nd November 2021) - Martínez Benedí, Pilar
ABSTRACT: This essay explores Melville's use of corporeality as a minor resistance to the spatial and conceptual containment of the naval discipline in White-Jacket . Seizing on the idea of porosity that this jacket encourages, it focuses on the body of its narrator in order to assess the role of an unbounded corporeality in the apprehension and narration of space. Relying on the Deleuzo-Guattarian distinction between striation and smoothness, the essay presents White-Jacket as a nomad that deterritorialises the space of the frigate as he writes.